PENINGKATAN HASIL BELAJAR IPA TENTANG GAYA MELALUI METODE EKSPERIMEN PADA SISWA KELAS IV A SDN EMPANG BAHAGIA 1 - Ayif, Syifa Fauziah; Waluyo Hadi; Endang Wahyudiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This Classroom Action Research aims to improve science learning outcomes in cognitive aspects. This research uses experimental learning methods in class IV A SDN Empang Bahagia 1. The subjects in this study were class IV A students totaling 28 students in the 2024/2025 school year. The research was carried out using the cycle model of Kemmis and Mc. Tagart through the stages of planning, implementation, observation and reflection. In cycle I, student learning outcomes showed a percentage of 64.28% and had not yet reached the specified percentage of success. In cycle II, student learning outcomes showed a percentage of 85.71%. The teacher action monitoring instrument in cycle I was 87% which increased in cycle II which was 100%. The student action monitoring instrument in cycle I, 80%, increased in cycle II, 93%. The implication in this study is that the experimental learning method can be used as one of the learning methods to improve science learning outcomes in grade IV elementary school students. With the experimental method, students are able to understand the material of force well, analyze the theory of force in everyday life, actively discuss with their groups, be able to present the results of group discussions and be able to conclude learning activities that have taken place in class with direct guidance by the teacher.